Post-Covid 19 Pandemic Online Taxi Business Relevance with an Efficiency Technical Analysis Approach - budi dharma; Marliyah (Jurnal Manajemen Sains dan Organisasi, 2023)
Purpose - The research aims to determine the condition of the taxi dare businessafter it was disrupted by the Covid-19 pandemic.Design/methodology/approach - Research was conducted on 100 brave taxibusiness owners operating in the city of Medan and using the frontier application asan analytical tool, followed by qualitative analysis to explain the results of thetechnical efficiency analysis.Findings - The conclusion of the research is that the current business condition isnot good, this can be seen from the inefficiency of most of the business owner'sproduction operations. The main factor for inefficiency is the value factor ofoperational assets/vehicles which greatly burdens production. This factor is theculmination of the impact of the Covid-19 pandemic which has caused businesses tolose money for more than a year. Other variables modeled in the production functionare information and technology variables and production support variables, thesetwo variables together become variables that support production efficiency. The research findings provide opportunities for deeper analysis, especially regardingstrategies to increase efficiency in the dare taxi business